Subtle cognitive deficits in severe alcohol addicts – Do they show a specific profile?. Issue 1 (29th October 2012) - Wollenweber, Frank A.; Halfter, Sarah; Brügmann, Elisabeth; Weinberg, Christina; Cieslik, Edna C.; Müller, Veronika I.; Hardwick, Robert M.; Eickhoff, Simon B.
<x xml:space="preserve">Abstract</x> Although alcohol dependency is a burden to society, data on cognitive performance in therapy‐resistant patients after multiple withdrawals are poor. In this study, 22 patients without reported cognitive deficits and 20 control subjects performed extensive cognitive testing and a motor task assessing short‐term memory. Patients displayed subtle deficits (mainly in executive function), while memory functions were relatively unimpaired. Our results suggest that subtle frontal‐executive deficits may contribute to a poor prognosis, but could be missed by routine clinical tests.